educationENGINEERINGMathematicsmathematics MTHtrigonometry equation

Show that Tan(A+B+C) = (tanA + tanB + tanC – tanAtanBtanC) ÷ (1-tanAtanB-tanBtanC-tanAtanC). Hence deduce that Tan3A = (3tanA-tan³A)/(1-3tan³A)

Trigonometry analytics

  1. Given that tan(A+B) = (tanA + tanB)/(1-tanAtanB). Show that Tan(A+B+C) = (tanA + tanB + tanC – tanAtanBtanC) ÷ (1-tanAtanB-tanBtanC-tanAtanC).
    Hence deduce that Tan3A = (3tanA-tan³A)/(1-3tan³A)
    Solvings
    Tan (A+B+C) = Tan[(A+B)+C]Let Tan(A+B) = Tanx
    Tan(X+C) = (Tanx + TanC)÷ (1-Tanxtanc)

Oluwamuyide Peter

My name is seyi, the main aim of creating this platform is to help users get information like school updates, electrical engineering topics, school project and many more for free

Related Articles

Leave a Reply

Back to top button